(untitled) (Research, Society and Development, 2022)
Objective: to identify the benefits of applying noninvasive post-extubation ventilation in adult patients without a specific cause for intubation. Methodology: this is an integrative literature review from the years 2017 to 2021 on research updates and analyzes on the use of this positive pressure ventilatory therapy in patients who were extubated. It was used as descriptors in the research “Noninvasive Ventilation”, “NIV”, “Extubation”, “Noninvasive Ventilation” and “Airway Extubation”. Based on selection criteria, only original studies and literature reviews published in this period were included, totaling 10 articles. Results: Invasive positive pressure ventilation was safe used during rest and in the first 48 hours after cardiac surgery, and improved gas exchange, oxygenation and hemodynamic stability. Therapy also reduced post-extubation ventilatory complications and minimized mortality and length of stay in intensive care units. Conclusion: more research and clinical trials with inclusion criteria, protocols for the use of non-invasive ventilation with positive pressure and more detailed respiratory and hemodynamic outcomes are needed, in order to point out the impacts and benefits of therapy on patients and help more carefully specify the patients who will benefit from use after extubation.